Evaluating occupational stress and coping mechanisms among prehospital emergency nurses: Review - Almunif, Sultan Kadisi; Alanazi, Awad Mohammed Awad; Al Maani, Mohammed Merza; Alotaibai, Abdullah Marzouq (International journal of health sciences, 2023)
Background: Occupational stress, particularly among prehospital emergency nurses, significantly impacts health outcomes and job performance. Factors such as high job demands, workplace violence, and inadequate training contribute to elevated stress levels, affecting mental health and employee retention. Methods: A systematic review was conducted using databases including PubMed, WOS, Enfispo, Cochrane, and LILACS to 2022. The search strategy focused on keywords related to "occupational stress" in nursing, specifically targeting prehospital care settings. A total of 14 studies were analyzed to categorize stressors and protective factors affecting emergency nurses. Results: The review identified five primary categories of stressors: management-related, patient care, interpersonal dynamics, environmental conditions, and personal factors. Notably, exposure to workplace violence and the emotional toll of pediatric emergencies were significant contributors to stress. Conversely, strong peer support and adequate managerial resources emerged as key protective factors. The findings suggest that 25% to 65% of prehospital nurses experience high levels of stress, largely influenced by their work environment and organizational responses. Conclusion: The study underscores the urgent need for improved training and support systems for prehospital emergency nurses to mitigate stress and enhance job satisfaction. Implementing mindfulness practices and addressing workplace violence can significantly improve the mental well-being of healthcare professionals.